A Protoplast Transient Expression System to Enable Molecular, Cellular, and Functional Studies in Phalaenopsis orchids - Lin, Hsiang-Yin; Chen, Jhun-Chen; Fang, Su-Chiung (Frontiers in Plant Science, 2018)
The enigmatic nature of the specialized developmental programs of orchids has fascinated plant biologists for centuries. The recent releases of orchid genomes indicate that orchids possess new gene families, family expansions and contractions to regulate a diverse suite of developmental processes. However, the extremely long orchid life cycle and lack of molecular toolkit have hampered the advancement of orchid biology research. To overcome the technical difficulties and establish a platform for rapid gene regulation studies, in this study, we developed an efficient protoplast isolation and transient expression system for Phalaenopsis aphrodite. This protocol was successfully applied to protein subcellular localization and protein-protein interaction studies. Moreover, it was confirmed to be useful in delineating the PaE2F/PaDP-dependent cell cycle pathway and studying auxin response. In summary, the established orchid protoplast transient expression system provides a means to functionally characterize orchid genes at the molecular level allowing assessment of transcriptome responses to transgene expression and widening the scope of molecular studies in orchids.